Unmasking trends and drivers of the international arachnid trade - Herzig, Volker; Hauke, Tobias J.; Lüddecke, Tim (Frontiers in Arachnid Science, 2023)
Introduction The global biodiversity crisis represents a major threat to humanity, with the worldwide animal trade being identified as a major driving force. Although vertebrate trade has been subject to intensified research, the extent of invertebrate trade remains understudied. Recent analyses of arachnids (i.e., spiders and scorpions) suggest that there is a large and still-expanding international market which has the potential to threaten natural populations. Whether or not captive breeding has the potential to decrease collection pressure on wild arachnid populations has not been investigated, nor have the temporal dynamics or the trade purposes of arachnids been examined. Methods We herein seek to broaden our understanding of these areas by analyzing arachnid import and export data from two major international wildlife trade databases (CITES and LEMIS). Results Historically, a large proportion of tarantulas and scorpions have been traded for the pet sector. Our analysis of the LEMIS data shows that imports of pet arachnids have declined by up to 55% in the past decade. Furthermore, an annual breakdown of US imports shows that at least 43% of specimens are not traded as pets but for other purposes, including research, souvenirs, and traditional medicine, with the souvenir sector experiencing an unprecedented growth. CITES data for protected tarantulas, but not scorpions, further indicate a shift toward trade with captive-bred specimens. Discussion These trends need to be considered in efforts to conserve natural populations. Coordinated captive breeding may represent a path toward increased sustainability by meeting the demand for traded arachnids and also providing an important resource for scientific research across disciplines.